Blood product transfusion and wastage rates in obstetric hemorrhage. Issue 6 (7th March 2018) - Yazer, Mark H.; Dunbar, Nancy M.; Cohn, Claudia; Dillon, Jessica; Eldib, Howida; Jackson, Bryon; Kaufman, Richard; Murphy, Michael F.; O'Brien, Kerry; Raval, Jay S.; Seheult, Jansen; Staves, Julie; et al.
Abstract : BACKGROUND: Bleeding emergencies can complicate pregnancies. Understanding the disposition of the products that are issued in this clinical setting can help inform inventory levels at hospitals where obstetric patients are seen. STUDY DESIGN AND METHODS: Patients who had an obstetric hemorrhage of any etiology between January 2013 and June 2017, and whose resuscitation began with uncrossmatched red blood cells (RBCs) or emergency‐issued plasma or platelets (PLT), were included. The disposition of all blood products issued within 6 hours of the first uncrossmatched or emergency‐issued product was documented, as was basic patient demographic information. RESULTS: In total, 301 women with an obstetric hemorrhage from seven academic institutions were identified. Their mean ± standard deviation age was 30.9 ± 6.1 years, 45.2% delivered by Cesarean section, and 40.5% delivered vaginally, while 12% did not deliver. The largest single etiology of hemorrhage was related to abnormal placentation. Of the 2280 issued RBC units, 55% were transfused, 43% were returned, and 2% were wasted. The rates of transfusion of the other blood products ranged from 58% for plasma units to 82% for cryoprecipitate. Seventeen percent of the issued cryoprecipitate units were wasted, the highest of any blood product. The rate of a patient receiving a transfusion when at least one blood product had been ordered ranged from 74% for PLTs to 91% for cryoprecipitate. CONCLUSION: Although the rates of receiving a transfusion of at least one blood product when one is ordered was high, many of the issued units were returned, especially for RBCs.